(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
A sol-gel process prepared the nanoparticles of hard cobalt ferrite (CoFe2O4). Cobalt nitrate hexahydrate (Co (NO3)2⋅6H2O), iron nitrate nonahydrate (Fe (NO3)3⋅9H2O) with using two catalysis acid (citric acid) and alkaline (hydroxide ammonium) were used as precursor materials. Crystallization behavior of the CoFe2O4 nanoparticles were studied by X-ray diffraction (XRD). Nanoparticles phases can change from amorphous to spinel ferrite crystalline depending on the calcinated temperature at 600°C, with using citric acid as a catalysis without finding forgone phase, while using hydroxide ammonium was shown second phase (α-Fe2O3) with CoFe2O4. Crystallite size was measured by Scherrer’s formula about (25.327) nm and (27.119) nm respectively. Structural properties were investigated by FTIR, which was appeared main bond of (Fe-O), (Co-O), (C-O), and (H-O). Scanning electron microscopy (FE- SEM) was shown the microstructure observation of cobalt ferrite and the particle size at the range about (28.77-42.97) nm. Magnetization measurements were carried out on a vibrating sample magenometer (VSM) that exhibited hard spinel ferrite.